Relative comparison of the benefits of wall envelope insulation materials in the South African energy zones, subject to the new national building energy efficiency standards - Kabundu, Emmanuel; Mbanga, Sijekula; Botha, Brink; Ayesu-Koranteng, Emma (Frontiers in Built Environment, 2024)
South Africa is ranked among the 20 highest greenhouse gas (GHG) emitters in the world, mainly due to its heavy reliance on coal for the generation of energy. The residential building industry can play a significant part towards both the minimization of GHG emissions and energy consumption, based on the materials and the fuels used in the material production and transportation. This research assesses the beneficial impacts of utilizing wall envelope insulation measures in form of five selected insulation materials at various levels of thickness, for a detached residential building, within the seven energy zones of South Africa in accordance with the South African National code for Building energy efficiency (SANS10400-XA). lifecycle energy savings implications of adopting the insulation materials is assessed together with the energy payback periods. The study area consisted of eight selected locations which together represent all the seven energy zones in South Africa (Welkom, Witbank, Thohoyandou, Cape Town, Pretoria, Ixopo, Sutherland, and Fraserburg). The analysis (lifecycle) period was 50 years. Based on the results for polyurethane, lower optimal insulation thicknesses tended to occur in locations with higher differences between summer and winter temperatures. Sutherland (zone 6) and Cape town (zone 4), and Fraserburg (zone 7) tended to benefit most in terms of energy savings due to application of insulation measures. Witbank (Zone 2), Thohoyandou (zone 3) and Pretoria (zone 5) tended not to benefit (in terms of energy savings) due to application of insulation measures. Cellulose and straw tended to correspond to lowest payback periods. Generally, polyurethane tended to yield highest net energy savings over lower insulation thickness levels, while cellulose was preferable over higher insulation thickness levels in Welkom (zone1) Cape Town (zone 4), Ixopo (zone 5H), Sutherland (zone 6) and Fraserburg (zone 7). However, literature shows that the selection of insulation material is also influenced by other concerns such as resistance to insect and mould attack (which easily affect bio-insulation materials), fire retardancy, durability (which affects cellulose), sound proofing, structural strength, and resistance to water vapour.